2018
DOI: 10.1080/17461391.2017.1420236
|View full text |Cite
|
Sign up to set email alerts
|

Impact of carbohydrate mouth rinsing on time to exhaustion during Ramadan: A randomized controlled trial in Jordanian men

Abstract: Mouth rinsing using a carbohydrate (CHO) solution has been suggested to improve physical performance in fasting participants. This study examined the effects of CHO mouth rinsing during Ramadan fasting on running time to exhaustion and on peak treadmill speed (V). In a counterbalanced crossover design, 18 sub-elite male runners (Age: 21 ± 2 years, Weight: 68.1 ± 5.7 kg, VO: 55.4 ± 4.8 ml/kg/min) who observed Ramadan completed a familiarization trial and three experimental trials. The three trials included rins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 59 publications
1
2
0
6
Order By: Relevance
“…The absence of changes in body mass and composition can be explained by our findings which identified a decline in daily training duration and intensity and the reduced exercise caloric expenditure which resulted in a comparable energy availability value. This result was in agreement with results from previous studies that reported no change in body mass during Ramadan fasting when comparable energy availability values were maintained ( 31 , 35 ). Additionally, Mujika ( 36 ) suggested that athletes and trained subjects could maintain their lean body mass and muscular strength after reducing training loads.…”
Section: Discussionsupporting
confidence: 93%
“…The absence of changes in body mass and composition can be explained by our findings which identified a decline in daily training duration and intensity and the reduced exercise caloric expenditure which resulted in a comparable energy availability value. This result was in agreement with results from previous studies that reported no change in body mass during Ramadan fasting when comparable energy availability values were maintained ( 31 , 35 ). Additionally, Mujika ( 36 ) suggested that athletes and trained subjects could maintain their lean body mass and muscular strength after reducing training loads.…”
Section: Discussionsupporting
confidence: 93%
“…They found no significant difference in mean HR (P = 0.03) between groups when comparing Ramadan and 1 month after Ramadan for small-sided games. This study indicated that RF combined with small-sided games and repeated-sprint ability training has no significant effect on most aerobic and anaerobic performances in male senior basketball players Bataineh et al [77] examined the effects of carbohydrate mouth rinsing during RF on running time to exhaustion and on peak treadmill speed. The study concluded that carbohydrate mouth rinsing improves running time to exhaustion and peak treadmill speed under RF conditions.…”
Section: Ramadan and Sportmentioning
confidence: 94%
“…En cuanto a volumen e intensidad de la carga se sabe que esta no siempre logra reflejar mejoras producto de que el rendimiento físico también es modulado por diversos principios del entrenamiento, además del componente cognitivo que puede generar mejoras independientemente de los cambios fisiológicos relacionados a la intensidad y volumen de la carga (Clarke, Hammond, Kornilios y Mundy 2017;Fuentes-Barría et al, 2020). Por otro lado, se sabe que un volumen de carga hasta el agotamiento o pruebas de extenuación no son muy efectivas producto de la transición generada desde el metabolismo glucolítico a lipídico como sustrato energético principal (Bataineh et al, 2018;Bavaresco Gambassi et al, 2019). Del mismo modo, entre las principales limitaciones de los diversos protocolos de enjuagues bucales con CHO se ha descrito a la demanda energética asociada a la intensidad y la tolerancia a la ingesta durante el ejercicio, siendo los protocolos que involucran un periodo prolongado de la solución al interior de la cavidad bucal los que pueden ocasionar molestias gastrointestinales o vómitos dificultando el proceso de inspiración y expiración (Ali, Moss, Yoo, Wilkinson y Breier, 2017;Pires et al, 2018).…”
Section: Discussionunclassified